2018
DOI: 10.1016/j.jbiomech.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The equivalence of multi-axis spine systems: Recommended stiffness limits using a standardized testing protocol

Abstract: The complexity of multi-axis spine testing often makes it challenging to compare results from different studies. The aim of this work was to develop and implement a standardized testing protocol across three six-axis spine systems, compare them, and provide stiffness and phase angle limits against which other test systems can be compared. Standardized synthetic lumbar specimens (n=5), comprising three springs embedded in polymer at each end, were tested on each system using pure moments in flexion-extension, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Previous studies demonstrated the importance of disc hydration, 3‐5 preload, 6‐9 and test rate 10‐15 . More recently, studies have compared biomechanical testing between laboratories, to investigate the application of pure moments to multi‐level spinal specimens 16 and to assess differences between six‐axis testing systems 17 . These studies have highlighted the importance of consistent methods for data processing, yet there is still a lack of consistency in specimen preparation and testing conditions used throughout the spinal community 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated the importance of disc hydration, 3‐5 preload, 6‐9 and test rate 10‐15 . More recently, studies have compared biomechanical testing between laboratories, to investigate the application of pure moments to multi‐level spinal specimens 16 and to assess differences between six‐axis testing systems 17 . These studies have highlighted the importance of consistent methods for data processing, yet there is still a lack of consistency in specimen preparation and testing conditions used throughout the spinal community 18 .…”
Section: Introductionmentioning
confidence: 99%
“…While a 400 N axial preload is commonly applied to the lumbar spine during in vitro ROM testing, a range of loads have been used depending on the in vivo loading condition being replicated. Axial compressive preloads may range from 0 to 250 N, 23,145,160‐166 350 to 500 N, 11,43,55,126,137,142,145,148,165,167,168 and greater than 500 N 26,55,92,95,150,151,155,167,169‐173 . For conditions to simulate in vivo bending of the lumbar spine, axial compressive preloads above 500 N are generated 144 depending on disc cross‐sectional area.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, an analysis of repeatability of methodologies, within or between laboratories is important to consider. 168,177,193,311 A number of these aspects were explored in the survey, which are summarized below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations